“Merciless Merciful Summer” by B. Melkevik: Collective Responsibility and Cancel Culture in Memorial Wars - D. S. Artamonov; S. V. Tikhonova (Теоретическая и прикладная юриспруденция)
This article describes the B. Melkevik’s philosophical and legal views on issues related to the legal understanding of collective memory, historical responsibility and collective guilt. The authors fit the researcher’s reasoning into the broad context of the development of ideas about collective responsibility and link the “ethical memory” criticized by B. Melkevik with the “cancel culture” and the spread of “new ethics”, suggesting the possibility of placing blame for the actions of one person on the group with which he identifies. The authors consider the limits of applicability of the concept of “Leta” B. Melkevik, believing that the conventional establishment of a regime of oblivion for historical memory through democratic procedures undermines the expertise of professional historical knowledge that provides a reliable Past. They come to the conclusion that the “cancel culture” characteristic of the digital media environment blocks the Habermas model of communicative rationality used by Melkevik.